The Influences of Attitude, Social Influence and Price Consciousness in Promoting Consumers’ Intention to Purchase Counterfeit Products - Nor Azila Mohd Noor; Azli Muhammad (International Journal of Supply Chain Management, 2019)
Counterfeiting has been proven to be a serious issue around the globe since the last few decades where counterfeiting is linked with varies of problems that causes chaos in economic activities and social life. This article sets out to examine factors influencing consumers’ intention to purchase counterfeit products. An intercept survey involving 390 respondents was conducted at three hot spot areas selling counterfeit products in Malaysia. A self-administered questionnaire was designed using established scales. This study utilized PLS-SEM to establish the validity and reliability of the measurement model and to test the hypotheses. The outcomes of this study show that intention to purchase counterfeit products is positively influenced by attitude and social influence of the consumers, while price consciousness does not significantly influence consumers’ intention to purchase counterfeit products. This study offers theoretical and practical contributions for academics and professionals. This study provides an understanding of consumers’ counterfeit purchase behavior of counterfeit products. The findings can be used by policy makers and genuine product producers to formulate strategies to curb counterfeiting activities.